2008
DOI: 10.1142/s0218863508004196
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation in Λ-Shaped Organic Molecules

Abstract: In epoxy based polymeric nonlinear optical (NLO) materials, the nonlinear optically active moiety forms crosslink between polymer chains. Some of the important moieties include 4, 4 diamino diphenyl sulfone (DADS). We have examined second harmonic generation (SHG) in DADS and have compared it with 4, 4 diamino diphenyl methane (DADM). The geometry optimization suggests that both molecules have Λ-shaped structure. The theoretical calculations as well as experimental observations of SHG in both the molecules sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The Λ shape is important for the design of BBUs without an inversion center and for packing of the BBUs into an NCS environment. Chemists have tailored organic and hybrid materials to Λ-shaped BBUs, as they have a high probability of packing into NCS crystals. ,,, For Λ-shaped organic molecules, such as N , N ′-bis­(4-ethoxycarbonylphenyl)­methaneiamin, minimization of intermolecular hydrogen bonds causes a preference for stacking of Λ-shaped units and synthesis of an NCS crystal structure . Similarly, our group has previously reported that minimizing contacts to the oxide ligand can lead to NCS, polar structures .…”
Section: Discussionmentioning
confidence: 99%
“…The Λ shape is important for the design of BBUs without an inversion center and for packing of the BBUs into an NCS environment. Chemists have tailored organic and hybrid materials to Λ-shaped BBUs, as they have a high probability of packing into NCS crystals. ,,, For Λ-shaped organic molecules, such as N , N ′-bis­(4-ethoxycarbonylphenyl)­methaneiamin, minimization of intermolecular hydrogen bonds causes a preference for stacking of Λ-shaped units and synthesis of an NCS crystal structure . Similarly, our group has previously reported that minimizing contacts to the oxide ligand can lead to NCS, polar structures .…”
Section: Discussionmentioning
confidence: 99%